Criminalization Policy for Child Sexual Offenses from the Perspective of Child Protection in Indonesia - Dioz Thimoteus Togatorop (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the criminal law policy against perpetrators of child sexual intercourse and legal protection efforts for victims based on the best interests of children in the Indonesian criminal system. Methodology: This research uses a normative legal method with a descriptive-analytical approach, using primary legal materials (Law No. 35 of 2014, Criminal Code, court decisions) and secondary (literature, journals), with analysis through statutory interpretation and content analysis. Results: Criminal law policies have been implemented in a formulative, applicative, and executive manner with preventive, repressive, and rehabilitative child protection, but their effectiveness is still hampered by structural and cultural constraints and limited child-friendly facilities. Conclusions: Criminal law policies regarding perpetrators of child sexual intercourse are comprehensive but not yet optimal; synergy between penal and non-penal approaches, regulatory reforms, and increased capacity of officials and public awareness are needed to achieve fair and child-friendly justice. Limitations: The research is normative in nature, so it does not reflect actual field conditions or the implementation of legal policies in practice, nor does it include comparison with other legal systems. Therefore, the findings are limited to conceptual and doctrinal analysis and require further empirical study. Contributions: This research strengthens the study of child protection-based criminal law and emphasizes the importance of criminal law reform towards a child-friendly justice system that focuses on the best interests of children.